2014
DOI: 10.1016/j.jstrokecerebrovasdis.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Clotting Factors to Treat Thrombolysis-related Symptomatic Intracranial Hemorrhage in Acute Ischemic Stroke

Abstract: Background Symptomatic intracranial hemorrhage (sICH) occurs uncommonly after ischemic stroke therapy with Tissue plasminogen activator (TPA). Clotting factor administration may be a treatment option. Objective To determine if treatment with clotting factors was associated with improved outcomes in sICH. Methods We conducted a retrospective cohort study within University of Texas at Houston Stroke registry involving consecutive patients from February 1, 2007 to June 30, 2011 with TPA related sICH; includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Existing studies of hemorrhage expansion after thrombolysis typically include only sICH and thus are weighted toward PH-2. Only 1 study considered radiographic type 83 and found that PH-2 represented ≈64% of sICH cases, but it could not clarify any differential risk of sICH expansion. Therefore, there is no evidence that different appearance of hemorrhage influences opportunity to benefit from treatment.…”
Section: Risk Of Hemorrhage Expansionmentioning
confidence: 98%
See 4 more Smart Citations
“…Existing studies of hemorrhage expansion after thrombolysis typically include only sICH and thus are weighted toward PH-2. Only 1 study considered radiographic type 83 and found that PH-2 represented ≈64% of sICH cases, but it could not clarify any differential risk of sICH expansion. Therefore, there is no evidence that different appearance of hemorrhage influences opportunity to benefit from treatment.…”
Section: Risk Of Hemorrhage Expansionmentioning
confidence: 98%
“…48,83,84 In 1 study of 128 alteplase-treated patients, nearly 80% of patients with sICH were diagnosed >2 hours after the alteplase infusion, and the median time from alteplase treatment to sICH diagnosis was nearly 8 hours. 48 Therefore, treating practitioners may consider extending the period of intensive (every 30 minutes) neurological and cardiovascular monitoring to 12 hours from the currently recommended 8 hours, particularly in patients with high risk for developing sICH.…”
Section: Timing Of Postthrombolytic Ichmentioning
confidence: 99%
See 3 more Smart Citations